Nutritional Assessment of the Area of Influence of the Marginal Highway III. Determination of ascorbic acid, thiamine, riboflavin and Nicotinamide - Guzmán Barrón, Alberto (1971)
Determination of Vitamin C or ascorbic acid in serum is used for diagnosing the states of serious deficit in food supply, which brings scurvy.